Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm having a little trouble with the following problem:

Calculate $F'(x)$:

$F(x)=\int_{1}^{x^{2}}(t-\sin^{2}t) dt$

It says we have to use substitution but I don't see why the answer can't just be:

$x-\sin^{2}x$

share|improve this question
    
You can apply the following rule (Leibnitz): If $I(t)=J(u,v,t)=\displaystyle\int_{u(t)}^{v(t)}f\left( x,t\right) dx,$ then, under suitable conditions, we have $I^{\prime }(t)=\displaystyle\int_{u\left( t\right) }^{v\left( t\right) }\dfrac{\partial f\left( x,t\right) }{\partial t}dx+f\left( v\left( t\right) ,t\right) v^{\prime}\left( t\right) -f\left( u\left( t\right) ,t\right) u^{\prime}\left( t\right) .$ –  Américo Tavares Oct 5 '10 at 23:12
add comment

5 Answers

up vote 17 down vote accepted

If you had $G(x)=\int_{1}^{x}(t-\sin^{2}t) dt$ (note that it's just $x$ at the upper limit of the integral), then $G'(x)=x-\sin^2x$. But, you have $F(x)=\int_{1}^{x^{2}}(t-\sin^{2}t) dt=G(x^2)$, so $F'(x)=G'(x^2)\cdot2x=(x^2-\sin^2x^2)2x$ (using the chain rule).

share|improve this answer
    
I get it now. Thanks! –  G.P. Burdell Oct 5 '10 at 22:53
add comment

You could apply the following more general rule (Leibniz rule and chain rule) -- although Isaac's answer is more straightforward for this derivative: If [edited in response to a Didier Piau's comment to this answer of mine]

$$I(x)=J(u(x),v(x),x),\quad \text{with}\ J(a,b,x)=\int_a^bf(t,x)dt,$$

then, under suitable conditions, we have

$$I^{\prime }(x)=\displaystyle\int_{u(x)}^{v(x)}\dfrac{\partial f(t,x)}{\partial x}dt+f(v(x),x)v^{\prime }(x)-f(u(x),x)u^{\prime }(x).$$

In this case:

$$F(x)=I(x)=\displaystyle\int_{1}^{x^{2}}(t-\sin ^{2}t)dt,$$

and

$$u(x)=1,\quad v(x)=x^{2},\quad f(t,x)=(t-\sin ^{2}t),$$

$$\dfrac{\partial f(t,x)}{\partial x}=0,\quad v^{\prime }(x)=2x,\quad u^{\prime }(x)=0.$$

Therefore

$$F^{\prime }(x)=I^{\prime }(x)=(x^{2}-\sin ^{2}x^{2})2x=2x^{3}-2x\sin ^{2}x^{2}.$$


The conditions are: $u(x),v(x)$ are differentiable functions, $f(t,x)$ is a continuous function and $\partial f/\partial x$ exists and is continuous.

share|improve this answer
add comment

Because the upper limit of the integral is x^2, not x.

share|improve this answer
add comment

Well according to me the answer is $$F'(x) = \frac{d}{dx}(x^{2}) \cdot [x^{2}-\sin^{2}(x^{2})] - \frac{d}{dx}(1) \times \text{something} = 2x \cdot \Bigl[x^{2} -\sin^{2}(x^{2})\Bigr] - 0$$ would be the answer.

share|improve this answer
add comment

$\displaystyle{% {{\rm d} \over {\rm d}x} = 2x\,{{\rm d} \over {\rm d}\left(x^{2}\right)} }$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.